2018
DOI: 10.1016/j.jhazmat.2018.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Removal of antiretroviral drugs stavudine and zidovudine in water under UV254 and UV254/H2O2 processes: Quantum yields, kinetics and ecotoxicology assessment

Abstract: The concentration of antiretroviral drugs in wastewater treatment plants (WWTP) effluents and surface waters of many countries has increased significantly due to their widespread use for HIV treatment. In this study, the removal of stavudine and zidovudine under UV photolysis or UV/HO was investigated in a microcapillary film (MCF) photoreactor, using minimal water samples quantities. The UV quantum yield of zidovudine, (2.357 ± 0.0589)·10 mol ein (pH 4.0-8.0), was 28-fold higher that the yield of stavudine (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 51 publications
1
18
0
1
Order By: Relevance
“…The results obtained in this study are similar to those reported by Russo et al (2018) [34] for antiretroviral nucleoside analogues stavudine and zidovudine belonging the same group of TDF. According to those studies, these drugs presented a weak inhibitory activity on Raphidocelis subcapitata growth, microalga specie very used in ecotoxicological studies.…”
Section: Toxicity Of Tdf To Cyanobacterium M Novacekiisupporting
confidence: 91%
“…The results obtained in this study are similar to those reported by Russo et al (2018) [34] for antiretroviral nucleoside analogues stavudine and zidovudine belonging the same group of TDF. According to those studies, these drugs presented a weak inhibitory activity on Raphidocelis subcapitata growth, microalga specie very used in ecotoxicological studies.…”
Section: Toxicity Of Tdf To Cyanobacterium M Novacekiisupporting
confidence: 91%
“…Studying AOPs' kinetics and degradation mechanisms of organics is of crucial importance in the design of novel or better-performing reactors and in their optimization [9]. This is usually realized through the estimation of intrinsic kinetic parameters in order to estimate the necessary treatment time [9][10][11]. Especially for heterogeneous catalytic systems, both immobilized and dispersed, different configurations can only be bridged by light-dependent intrinsic kinetics [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors suggested the possibility of direct use of these devices for water treatment by numbering up units [25,42], this seems a fairly unrealistic and antieconomic scenario, with very few possible niche applications in the treatment of small volumes of water for specific applications. Only a limited number of papers have addressed the use of microreactors for the estimation of intrinsic parameters and mechanism identification, which can be used for the scale-up of AOPs for wastewater treatment, which, in fact, is the most promising application [9,11,12,23,[43][44][45][46][47][48][49][50][51][52][53][54]. In this sense, there is still extensive room for improvement and exploitation of this technology for the design and scale-up of such tertiary treatments.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Owing to their unique structure and relatively low cost, MCFs have been proven useful for generating in parallel multiple individual fluid drops or crystals, [ 6,7 ] photoreactions, and sound absorption. [ 8,9 ] Furthermore, an alternative structure, namely, MCFs with interconnected pores, was fabricated by Bonyadi and Mackley through a solution extrusion followed by a nonsolvent induced phase separation process out of an ethylene vinyl alcohol (EVOH) copolymer. [ 10 ] This new type of structure is called a microporous‐walled micro‐capillary film (MMCF), the characteristics of which are films with multiple embedded hollow capillaries interconnected with pores (0.1–20 µm) in a matrix.…”
Section: Introductionmentioning
confidence: 99%